Diketopyrrolopyrrole-polymer meets thiol-ene click chemistry: a cross-linked acceptor for thermally stable near-infrared photodetectors - Casutt, Manuela; Koser, Silke; Bunz, Uwe H. F.; Jänsch, Daniel; Freudenberg, Jan (Chemistry of materials, 2019)
A problem of bulk-heterojunction (BHJ) organic photodetectors (OPDs) is the morphological instability arising from segregation and demixing of its donor and acceptor components. To stabilize the morphology of the blended active layer we synthesized a cross-linkable low-band-gap 1,4-diketopyrrolo[3,4-c]pyrrole (DPP)-based donor-acceptor (DA) copolymer with ω-alkenyl side chains. Due to its absorption cutoff above 1000 nm we employed it as an acceptor material in a solution-processed BHJ near-infrared-OPD with P3HT as a donor. Photochemical in situ thiol-ene click chemistry using a tetrathiol as an additive cross-linker renders the BHJ insoluble to organic solvents and stable under accelerated thermal aging.
Gesehen am 29.10.2019